Radiology Information Systems: Basic Principles and Current Practice - Lehr, James L. (1981)
Because radiology represents a sizeable financial and operational component of any health care delivery system, the needs for and opportunities provided by a radiology information system should be carefully considered in planning any medical data processing system. Experience with such systems over the past fifteen years has demonstrated that they can improve service quality and save money. The functions which can be performed by radiology computer systems are relatively well defined and will be presented during the morning session of this workshop. Eleven of the systems which are currently in operation, several of which can be acquired from vendors, will be discussed in the afternoon.